Spectroscopic measurements and terahertz imaging of the cornea using a rapid scanning terahertz time domain spectrometer - 刘文权 鲁远甫 焦国华 陈险峰 周志盛 佘荣斌 李金瑛 陈四海 董玉明 吕建成 (Chinese physics B, 2016)
Spectroscopic measurements and terahertz imaging of the cornea are carried out by using a rapid scanning terahertz time domain spectroscopy（THz-TDS） system.A voice coil motor stage based optical delay line（VCM-ODL） is developed to provide a rather simple and robust structure with both the high scanning speed and the large delay length.The developed system is used for THz spectroscopic measurements and imaging of the corneal tissue with different amounts of water content,and the measurement results show the consistence with the reported results,in which the measurement time using VCM-ODL is a factor of 360 shorter than the traditional motorized optical delay line（MDL）.With reducing the water content a monotonic decrease of the complex permittivity of the cornea is observed.The two-term Debye relaxation model is employed to explain our experimental results,revealing that the fast relaxation time of a dehydrated cornea is much larger than that of a hydrated cornea and its dielectric behavior can be affected by the presence of the biological macromolecules.These results demonstrate that our THz spectrometer may be a promising candidate for tissue hydration sensing and practical application of THz technology.